An injectable and self-strengthening nanogel encapsuled hydrogel gene delivery system promotes degenerative nucleus pulposus repair. (1st February 2023) - Wang, Yu; Zheng, Cheng; Wu, Ye; Zhang, Bo; Hu, Cheng; Guo, Chuan; Kong, Qingquan; Wang, Yunbing
Abstract: Local inflammatory responses, a gradual imbalance in anabolic/catabolic activities as well as progressive functional impairment within the nucleus pulposus (NP) are responsible for the progression of intervertebral disc degeneration (IDD). Antagomir-21, a cholesterol-modified inhibitor of miRNA-21, has the potential to regenerate the extracellular matrix (ECM), but the absence of suitable delivery systems limits its applications for IDD treatment. In this study, one type of antagomir-21-loaded nanogel (NG@antagomir-21) was encapsulated in injectable self-strengthening hydrogel gene delivery system for the controlled and sustained delivery of the drug into the NP for over 14 days. The hybrid hydrogel also displayed intelligent and sustained release of antagomir-21 via a three-stage mechanism. The hydrogels were designed to be easily injected into the intervertebral disc with lower mechanical strength. After a strength-enhancing process, the resulting fully gelatinized hydrogels of higher mechanical strength had the ability to prevent leakage, provide sufficient mechanical support and maintain the stability of the spinal segment. In addition, the physicochemical properties of the hybrid hydrogels as well as their excellent biocompatibility, degradability, anti-inflammatory effects and strong ability to regulate the ECM's metabolic balance in vitro were demonstrated. In vivo testing highlighted the synergy between the anti-inflammatory and ECM regenerative effects effectively promoted the hydrogels' efficacy for IDD therapy. This hydrogel gene delivery system showed great promise for applications in IDD repair. Graphical abstract: Image 1 Highlights: The hydrogel showed desirable strength-engancing property after injecting into IVD. Antagomir-21 was loaded in MMP-sensitive nanogel via host-guest interactions. Antagomir-21 would intelligent and sustained release via a three-stage mechanism. Internalization of antagomir-21 effectively promoted ECM regeneration of NPCs. The anti-inflammation and ECM regeneration behavior of hydrogel promoted IDD repair.